Interregional Risk Sharing and Fiscal Redistribution in Reunified Germany - Falko Jüßen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
This paper provides empirical evidence of interregional risk sharing in reunified Germany. The focus is on two related questions: First, to what extent do private institutions and the public sector provide insurance against asymmetric shocks to individual regions? Second, to what extent does the public sector reduce long-term dierences between regions? While the federal government channel is not found to have a stabilizing eect, private factor income flows provide almost complete insurance against short-term shocks. In sharp contrast, the fiscal transfer system achieves a substantial reduction of long-term disparities between regions. These results show that fiscal transfers in reunified Germany are mainly concerned with redistribution in favor of depressed regions rather than providing insurance against idiosyncratic shocks.
Keywords: H23; O47; R11; E63; 519; interregional risk sharing; fiscal redistribution; distribution dynamics; regional disparities